Brew Crypto - Salehhudin, Noorhidayah; Ahmad Suki, Amirah (IIUM Journal of Case Studies in Management, 2025)
This case study delves into the journey of "Brew Crypto," a small coffee shop that has embraced cryptocurrency, navigating through the complexities of digital transactions to enhance customer experience and operational efficiency. By exploring Brew Crypto’s strategic implementation of blockchain technology, this research highlights the challenges, opportunities, and impacts of integrating digital currencies into small business operations.